PERLINDUNGAN HUKUM TERHADAP PENGGUNA APLIKASI WHATSAPP DALAM KEWAJIBAN PENYERAHAN DATA PRIBADI - Yusqi Alfan Thoriq; Dipo Wahyoeono (Gapenas Publisher, 2022)
This research focuses on the Whatsapp application, Whatsapp is one of the short message telecommunications based on internet applications which in today's digital era most people certainly know a lot about Whatsapp, an example of a real thing and is still often the case, is the leakage of personal data. experienced by a person or community groups, in the end the data leakage This research was made using the Normative Legal Research method. Until now there has been no legislation that concretely regulates the protection of personal data in the State of Indonesia. Thus causing a vacuum of legal norms. There is still a lack of supervision from the Government regarding personal data managed by websites or applications originating from outside Indonesia. The government and the House of Representatives should immediately ratify the Personal Data Protection Law, so that there is no legal norm vacuum. The government must improve the quality of human resources in the process of collecting and managing personal data so that there is no leakage of personal data